From Standard of Care to Emerging Innovations: Navigating the Evolution of Pharmacological Treatment of Gestational Diabetes - Palatnik, Anna; Feghali, Maisa N. (American Journal of Perinatology, 2024)
The incidence of gestational diabetes mellitus (GDM) continues to increase in the United States and globally. While the first-line treatment of GDM remains diet and exercise, 30% of patients with GDM will require pharmacotherapy. However, many controversies remain over the specific glycemic threshold values at which pharmacotherapy should be started, how intensified the therapy should be, and whether oral agents are effective in GDM and remain safe for long-term offspring health. This review will summarize recently completed and ongoing trials focused on GDM pharmacotherapy, including those examining different glycemic thresholds to initiate therapy and treatment intensity.
Keywords: gestational diabetes; pharmacologic treatment; insulin; metformin; incretins